Agricultural residue‐derived lignin as the filler of polylactic acid composites and the effect of lignin purity on the composite performance. Issue 35 (2nd May 2019) - Gao, Yiwei; Qu, Wangda; Liu, Yang; Hu, Hui; Cochran, Eric; Bai, Xianglan
ABSTRACT: In this study, corn stover lignin with different purities was used as filler in polylactic acid (PLA) matrix. It was found that the impurity metals present in unpurified lignin can significantly affect the performance of the composites in terms of their thermal stability, rheological behavior, mechanical properties, and hydrophobicity. Among the PLA composites, the ones fabricated with the lignin containing 4% of impurities overall had the best thermal stability and tensile strength. From melt rheology analysis, it was also found that the presence of the impurity metals decreases the complex viscosity of the composites. It is suggested that the impurity metals acted as catalysts to promote the interaction between lignin and PLA, resulting in an improved compatibility between PLA and the filler. In the present study, mechanical properties and hydrophobicity of the composites were further improved by acetylating the lignin with the optimum content of impurities. Tensile strength of the composite with the acetylated lignin was comparable to that of pure PLA, whereas the modulus increased to as high as 2.75 GPa. Overall, the study showed that unpurified lignin could be used as filler to achieve similar or better performance than the composites made with highly purified lignin fillers. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47915. Abstract :